2008
DOI: 10.1128/jcm.01542-07
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Epidemiology of Escherichia coli Producing Extended-Spectrum β-Lactamases Isolated in Rome, Italy

Abstract: Escherichia coli strains producing extended-spectrum ␤-lactamases (ESBLs) are a major problem in many different hospitals worldwide, causing outbreaks as well as sporadic infections. The prevalence of Escherichia coli ESBL producers was analyzed in a surveillance study performed on the population attending the Policlinico Umberto I, the largest university hospital in Rome, Italy. We also investigated genotypes, pathogenicity islands, and plasmids in the ESBL-positive E. coli isolates as further markers that ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

11
38
1
2

Year Published

2008
2008
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 104 publications
(52 citation statements)
references
References 32 publications
11
38
1
2
Order By: Relevance
“…The FII-type plasmids were probably specific for each of these PFGE types as shown by differences in their mating ability and transferable resistance markers. A number of reports demonstrated the strong link between bla CTX-M-15 and FII-type plasmids (7,11,23,24,33). These molecules often carry also bla OXA-1 , bla TEM-1 , and aac(6Ј)-Ib-cr genes, which was confirmed in this work by specific PCRs (11) and sequencing ( Table 1).…”
supporting
confidence: 66%
“…The FII-type plasmids were probably specific for each of these PFGE types as shown by differences in their mating ability and transferable resistance markers. A number of reports demonstrated the strong link between bla CTX-M-15 and FII-type plasmids (7,11,23,24,33). These molecules often carry also bla OXA-1 , bla TEM-1 , and aac(6Ј)-Ib-cr genes, which was confirmed in this work by specific PCRs (11) and sequencing ( Table 1).…”
supporting
confidence: 66%
“…which is also in corroboration with reports by others worldwide (17)(18)(19)(20). As in the present study, a higher prevalence of the bla CTX-M-1 gene than of the bla SHV gene has been reported, which may be due to the wide use of extended-spectrum cephalosporins in India, especially ceftriaxone and cefotaxime, or it may be associated with the high mobilization of the encoding genes (21,22,23,24).…”
supporting
confidence: 82%
“…If this small subgroup is to be considered representative of the organisms currently involved in the development of SBP, our study supports the possibility that, in recent years, the microbial etiology of SBP is changing, as it seems to have more generally occurred for bacterial infections of these kinds of patients [14] . In our hospital, a recent survey [36] on 4769 samples collected for bacterial isolation from April to September 2006, showed a high prevalence of ESBL-producing enterobacteriacae as an emergent cause of infections. In particular, among the ESBL-positive E. coli, strains with CTX-M -lactamases, specifically able to hydrolyze cefotaxime, were the most diffused.…”
Section: Discussionmentioning
confidence: 99%